If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7(-3x + 4) = 136 Reorder the terms: 3x + 7(4 + -3x) = 136 3x + (4 * 7 + -3x * 7) = 136 3x + (28 + -21x) = 136 Reorder the terms: 28 + 3x + -21x = 136 Combine like terms: 3x + -21x = -18x 28 + -18x = 136 Solving 28 + -18x = 136 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + -18x = 136 + -28 Combine like terms: 28 + -28 = 0 0 + -18x = 136 + -28 -18x = 136 + -28 Combine like terms: 136 + -28 = 108 -18x = 108 Divide each side by '-18'. x = -6 Simplifying x = -6
| 9=7m-5 | | x((x^2)+5x-16)=-80 | | (x^3)+(5x^2)-16x-80=0 | | 8t+8t=1504 | | 7.6-2.3X=159 | | 4/3=6/(x+5) | | -4.21+x=-19 | | 12x+12=15x+75 | | 6x^2+23x-18/4x^2+36x+81 | | 5x-19=6x+7 | | 9t-7=25+t | | 0=x^2+7x+1 | | 9x-(3x+6)=42 | | F(x)=x^2+7x+1 | | -8=6x-14/7 | | 9x^2+64=49 | | 6=-3/5(-3)+6 | | -4x-6(-3x-5)=114 | | -17x-204= | | 2z-14=20 | | -3X-11=70 | | 84=x/3 | | 34=w/2 | | 5=(-5x+10x)+80 | | (2k-5)(k+2)=-9 | | 5b+3/4b=85 | | .12x+.60(6-x)=2.4 | | 3-7(x+4)=28 | | x/5+5=8 | | 2+3x=12+2 | | 19+8.3/4= | | 5j+j=5124 |